Optimised PLGA–fucoidan–PDMS composite scaffolds for bone tissue engineering: improved mechanical and structural performance - Izdihar Kamal; Nurhidayah Mohd Hapipi; Mohd Hafiz Mohd Zaid; Nazathul Syazliyana Khairul; Norshazliza Abdul Ghani; Loh Zhi Wei; Nur Zawani Saharuddin; Aminatul Saadiah Abdul Jamil; Hatikahaty Mohammad Diah; Khairiah Abdul Hamid; Muhammad Khalis Abdul Karim (Springer Nature, 2026)
Indexed by WOS / SCOPUS / ERA